Efficacy of adjunctive photodynamic therapy to conventional mechanical debridement for peri-implant mucositis - Guo, Jincai; Chen, Xueru; Xie, Hui; Li, Tongjun (BMC oral health, 2024)
This meta-analysis was conducted to assess the effectiveness of photodynamic therapy (PDT) as an adjunct to conventional mechanical debridement (CMD) for the management of peri-implant mucositis (p-iM). We systematically searched four databases (PubMed, Embase, Web of Science, and Cochrane Library) for randomized controlled trials (RCTs) investigating PDT + CMD for p-iM from their inception to March 13, 2023. Meta-analysis was performed using RevMan 5.4 software. Seven RCTs met the inclusion criteria. The meta-analysis revealed that PDT + CMD treatment was more effective than CMD alone in reducing probing depth (PD) (Mean Difference [MD]: -1.09, 95% Confidence Interval [CI]: -1.99 to -0.2, P = 0.02) and plaque index (PI) (MD: -2.06, 95% CI: -2.81 to -1.31, P < 0.00001). However, there was no statistically significant difference in the improvement of bleeding on probing (BOP) between the PDT + CMD groups and CMD groups (MD: -0.97, 95% CI: -2.81 to 0.88, P = 0.31). Based on the current available evidence, this meta-analysis indicates that the addition of PDT to CMD significantly improves PD and PI compared to CMD alone in the treatment of p-iM. However, there is no significant difference in improving BOP.